148 Cardiac myosin-binding protein C to diagnose acute myocardial infarction in the pre-hospital setting, using multi-factorial nomograms. (May 2019) - Kaier, Thomas; Stengaard, Carsten; Marjot, Jack; Sørensen, Jacob Thorsted; Alaour, Bashir; Stavropoulou-Tatla, Stavroula; Terkelsen, Christian Juhl; Williams, Luke; Thygesen, Kristian; Weber, Ekkehard; Marber, Michael; Bøtker, Hans Erik
Abstract : Background: Early triage is essential to improve outcome in patients with suspected Acute Myocardial Infarction (AMI). This study investigated whether cardiac myosin-binding protein C (cMyC), a novel biomarker of myocardial necrosis, can aid early diagnosis of AMI and risk stratification. Methods: cMyC and hs-cTnT were retrospectively quantified in blood samples obtained by ambulance-based paramedics in a prospective, diagnostic cohort study. Patients with ongoing or prolonged periods of chest discomfort, acute dyspnoea in the absence of known pulmonary disease, or clinical suspicion of AMI were recruited. Discrimination power was evaluated by calculating the Area under the Receiver-operating characteristics curve; diagnostic performance was assessed at pre-defined thresholds. Diagnostic nomograms were derived & validated using bootstrap resampling in logistic regression models. Results: 776 patients with median age 68 [58;78] were recruited. AMI was the adjudicated diagnosis in 22%. Median symptom to sampling time was 70 minutes. cMyC concentration in patients with AMI was significantly higher than with other diagnoses: 98 [43;855] vs 17 [9;42] ng/L. Discrimination power for AMI was better with cMyC than with hs-cTnT: AUC 0.839 vs 0.813 (p=0.005). At a previously published rule-out threshold (10 ng/L), cMyC reaches 100% sensitivity and NPV in patients after 2 hours of symptoms. In logistic regression analysis, cMyC is superior to hs-cTnT and was used to derive diagnostic and prognostic nomograms to evaluate risk of AMI and death (figure 1 ): the nomogram for diagnosis of AMI incorporates easily accessible clinical information plus two biomarker values (cMyC and creatinine) into a probability score for AMI at presentation. When modelling the probability of death during 2-year follow-up, cMyC followed a non-linear curve, with marked variation depending on age and prior myocardial infarction (figure 2 ). Conclusion: In the prehospital setting, cMyC demonstrates improved diagnostic discrimination of AMI and could significantly improve the early triage of patients with suspected AMI. Conflict of Interest: None